OLIGOCENE CLAY MINERALOGY OF THE LINXIA BASIN: EVIDENCE OF PALEOCLIMATIC EVOLUTION SUBSEQUENT TO THE INITIAL-STAGE UPLIFT OF THE TIBETAN PLATEAU - Hong H.; Li Zh.; Xue H.; Zhu Yu.; Zhang K.; Xiang Sh. (My University, 2007)
The clay mineral content of the Oligocene sediments in the Linxia Basin has been investigated using X-ray diffraction, scanning electron microscopy, and high-resolution transmission electron microscopy. The clay mineral assemblages are mainly mixed-layer illite-smectite (I-S), illite, kaolinite and minor palygorskite in the early-Middle Oligocene deposits, mixed-layer I-S, illite and kaolinite in the Middle Oligocene deposits, mainly illite and chlorite (usually >50–70 vol.%), mixed-layer I-S, and trace to minor palygorskite in the late Oligocene sediments, respectively. The mineral assemblage indicates a warm and seasonally humid climate in the Middle Oligocene, with an episode of warm and dry conditions in the early stage of the Middle Oligocene, and a trend of temperature decrease and more arid conditions in the late Oligocene. Climate evolution in the Oligocene corresponds with the significant elevation change in central Tibet since late Oligocene, and therefore, suggests that tectonic-forced cooling of climate took place in Linxia in the northeast margin of the Tibetan Plateau. The ubiquitous mixed-layer I-S and carbonates throughout the Oligocene sediments reflect relatively small fluctuations in climate conditions during the epoch. The changes in clay mineral components and feldspars in the late Oligocene suggest a variation in the source of clastic materials, which probably reflects an increase in erosion of soils and poorly weathered parent rock in more elevated or high-relief source areas during this period of tectonic uplift.
Keywords: CHINA; CLAY MINERALS; LINXIA BASIN; OLIGOCENE; PALYGORSKITE; TIBETAN PLATEAU; UPLIFT; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен